THE EFFECT OF PHYSICAL WORK ENVIRONMENT, NON-PHYSICAL WORK ENVIRONMENT, AND ROLE CONFLICT ON INTENTION TO QUIT (Study on Employees of PT X) - Pramesti, Fadiyah Indah; Yuniawan, Ahyar (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
The purpose of this research is to investigate the factors of intention to quit, which is the final decision made if the employee is dissatisfied with the job and its environment. This includes the physical work environment, non-physical work environment, and role conflict experienced by employees. This research uses quantitative methods with data processing using the Smart PLS version 4 application, with 100 respondents from PT X. Based on the research that has been conducted, it is known that the physical work environment has a negative and insignificant effect on intention to quit so that H1 is rejected, the non-physical work environment has a positive and insignificant effect on intention to quit so that H2 is rejected, and role conflict has a positive and significant effect intention to quit so that H3 is accepted. Overall, this study highlights the importance of both physical and non-physical work environments and role conflict in influencing employee’s intention to quit. Although the results of the statistical analysis did not always show a significant relationship, respondents' responses consistently indicated that comfortable working conditions, good interpersonal relationships, a positive organizational culture, and minimal role conflict can contribute to a decrease in employee’s intention to quit.